Transformative consumer service: Toward a better tourism enjoyment for tourists with disabilities - Moufakkir, Omar (Téoros)

(untitled) (Université du Québec à Montréal, 2013)
Despite progress in the inclusion of people with disabilities in society and in leisure participation, including access to tourism, their satisfaction with the tourism experience is still an area that receives limited attention in tourism research. Ingrained in the social psychology of tourism studies, the purpose of this study is to adapt the leisure constraints model to fill this gap and contribute positively to the tourism experience of this market segment. A questionnaire based on the literature was administered to a sample of people with various types of disabilities, to assess the importance of certain constraints on enjoyment, and highlight the importance of certain criteria for enjoyment. Findings support submissions that this market is a viable tourist segment based on travel frequency, preference for domestic travel, and information sources. Slight differences among disability groups regarding perceived constraints, problems encountered when travelling, inclusion, and important criteria for enjoyment are recorded.